Health & Social Care - Nolan, Yvonne; Burgess, Colette; Shaw, Colin (Harlow, Essex : Heinemann, 2011)
Heinemann offers a total solution for those taking and delivering the new Level 2 qualification in health and social care, supporting candidates in their qualification so that they in turn can support others.
Includes index.
Keywords: Public health; Social service; Society